Composite catalyst, its preparation method and application
Patent Information
- Application Number
- CN202410293278.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-03-14
AI Technical Summary
然而现有方法采用的是常规的钯碳催化剂进行加氢反应,催化效率低,产物产量低、纯度低
[0030]本发明中碳基钌/钯/锆复合催化剂,采用自制活性炭载体,具有广阔的比表面积,为活性离子钌提供了富足的附着位点,进而使本发明有充足的反应活性位点。同时,本发明对原料中上C=O的加氢有抑制作用,降低了酰类化合物深度加氢产物的生成,同时减少聚合物的生成。并且相较于现有的催化剂,本发明提供的碳基钌/钯/锆复合催化剂催化还原活性更高,效果更好。
Smart Images

Figure CN118341422B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a composite catalyst, its preparation method, and its application, belonging to the field of hydrogenation catalyst technology. Background Technology
[0002] Furfural residue is a waste byproduct generated during the commercial production of furfural, with approximately 13 tons of residue produced for every ton of furfural produced. The annual emissions of furfural residue are enormous, reaching 2.4 to 3 million tons in China. This massive amount of furfural residue poses a significant threat to the environment. If this residue could be utilized rationally, it would improve the economic efficiency of industrial furfural production.
[0003] Diamino compounds containing aromatic rings in their molecular structure are important raw materials for preparing high-temperature resistant polyimide polymers, carbon fiber reinforced composite matrix resins, liquid crystal alignment agents, and passivation coatings for ultra-large-scale integrated circuits. 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane is a particularly important type of diamino compound containing aromatic rings and has a broad market prospect.
[0004] Currently, the most common method for preparing 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane in existing technologies is a two-step process: Step 1: Using 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP) and p-nitrobenzoyl chloride as raw materials, a low-temperature reaction in a mixed solvent is carried out to obtain the intermediate dinitro compound: 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane. Step 2: The intermediate dinitro compound is then hydrogenated on palladium on carbon or reduced with hydrazine hydrate to synthesize 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane. However, existing methods use conventional palladium on carbon catalysts for the hydrogenation reaction, resulting in low catalytic efficiency, low product yield, and low purity.
[0005] Therefore, there is an urgent need to develop a composite catalyst with high catalytic efficiency and apply it to the preparation of products such as 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a composite catalyst, its preparation method, and its application.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a composite catalyst includes the following steps:
[0009] S1: Furfural residue lignin is suspended in H3PO4 solution and stirred at 20-30℃ for 5-8 hours. Then it is dried, carbonized and quenched to obtain crude activated carbon. HCl solution is added to the crude activated carbon and heated to 45-65℃ for 20-40 minutes. After washing, drying and grinding, carrier activated carbon is obtained.
[0010] S2: Add the activated carbon support prepared in step S1 to a ruthenium nitrate solution, stir and react for 3-10 h, filter, sonicate the filtered product in water for 10-20 min, filter again to obtain parent material 1; add parent material 1 to a palladium nitrate solution, stir and react for 3-10 h, filter, sonicate the filtered product in water for 10-20 min, filter again to obtain parent material 2; add parent material 2 to a zirconium nitrate solution, stir and react for 2-6 h, filter, sonicate the filtered product in water for 10-20 min, filter again, and dry to obtain the composite catalyst precursor;
[0011] S3: The composite catalyst precursor prepared in step S2 is calcined at 500℃ for 3h, and then the calcined composite catalyst precursor is transferred to a fixed bed reactor. Hydrogen gas at 6MPa is introduced at 200℃ for reduction reaction. When the reduction temperature of the fixed bed reactor no longer changes, the temperature is maintained for 30min. After washing and drying, carbon-based ruthenium / palladium / zirconium composite catalyst is obtained.
[0012] According to a preferred embodiment of the present invention, in S1, the mass ratio of furfural residue lignin to H3PO4 solution is 1:6; and the concentration of H3PO4 solution is 25-35%.
[0013] According to a preferred embodiment of the present invention, in S1, the carbonization specifically involves heating the dried product to 550°C in a muffle furnace at a heating rate of 15°C / min, and then holding it at 550°C for 3 hours to complete the carbonization.
[0014] According to a preferred embodiment of the present invention, in S1, the concentration of the HCl solution is 0.1M; the volume-to-mass ratio of the HCl solution to furfural residue lignin is 15:1, in mL / g.
[0015] According to a preferred embodiment of the present invention, in S2, the mass ratio of the carrier activated carbon to the ruthenium nitrate solution is 1:(4-8); the concentration of the ruthenium nitrate solution is 2-8 mol / L; and the stirring reaction time is 3-6 h.
[0016] More preferably, the mass ratio of the carrier activated carbon to the ruthenium nitrate solution is 1:6; the concentration of the ruthenium nitrate solution is 5-6 mol / L; and the stirring reaction time is 4 h.
[0017] According to a preferred embodiment of the present invention, in S2, the mass ratio of the carrier activated carbon to the palladium nitrate solution is 1:(4-8); the concentration of the ruthenium nitrate solution is 2-4 mol / L; and the stirring reaction time is 3-6 h.
[0018] More preferably, the mass ratio of the carrier activated carbon to the ruthenium nitrate solution is 1:5; the concentration of the ruthenium nitrate solution is 2.5–3 mol / L; and the stirring reaction time is 5 h.
[0019] According to a preferred embodiment of the present invention, in S2, the mass ratio of the carrier activated carbon to the zirconium nitrate solution is 1:(4-8); the concentration of the ruthenium nitrate solution is 3-7 mol / L; and the stirring reaction time is 3-6 h.
[0020] More preferably, the mass ratio of the carrier activated carbon to the ruthenium nitrate solution is 1:7; the concentration of the ruthenium nitrate solution is 4.5–5 mol / L; and the stirring reaction time is 6 h.
[0021] According to a preferred embodiment of the present invention, in step S3, the composite catalyst precursor is calcined at 500°C for 3 hours.
[0022] According to a preferred embodiment of the present invention, in step S3, hydrogen gas at 6 MPa is introduced at 200°C to carry out the reduction reaction.
[0023] This invention provides a carbon-based ruthenium / palladium / zirconium composite catalyst prepared by the above method.
[0024] This invention also provides the application of the above-mentioned carbon-based ruthenium / palladium / zirconium composite catalyst in the preparation of 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
[0025] According to a preferred embodiment of the present invention, the application specifically includes:
[0026] 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane was dissolved in an organic solvent, and hydrogen gas was continuously introduced to maintain a reaction pressure of 0.5 MPa. Then, the aforementioned carbon-based ruthenium / palladium / zirconium composite catalyst was added, and the reaction was carried out at 25 °C and a liquid hourly space velocity of 50 h⁻¹. -1 The reaction was carried out under the conditions for 0.5–1 h to obtain 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
[0027] More preferably, the amount of the carbon-based ruthenium / palladium / zirconium composite catalyst added is 0.5 to 1.5% of the mass of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane; most preferably, it is 1%.
[0028] Where this invention is not detailed, existing technologies may be used.
[0029] The beneficial effects of this invention are as follows:
[0030] The carbon-based ruthenium / palladium / zirconium composite catalyst of this invention uses a self-made activated carbon support with a wide specific surface area, providing abundant attachment sites for active ruthenium ions, thus ensuring sufficient reactive sites. Simultaneously, this invention inhibits the hydrogenation of C=O in the feedstock, reducing the formation of deep hydrogenation products of acyl compounds and decreasing polymer formation. Furthermore, compared to existing catalysts, the carbon-based ruthenium / palladium / zirconium composite catalyst provided by this invention exhibits higher catalytic reduction activity and better performance. Attached Figure Description
[0031] Figure 1 The images shown are SEM and EDS images of the carbon-based ruthenium / palladium / zirconium composite catalyst structure described in Example 1 of this invention.
[0032] In the image, the left image is the SEM image, and the right image is the EDS image.
[0033] Figure 2 The liquid phase diagram shows the purity of 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane prepared in Example 5 of this invention. Detailed Implementation
[0034] The present invention will be further described in detail below with reference to specific embodiments, but this should not be construed as limiting the invention. Experimental methods and reagents not specified in the embodiments, unless otherwise stated, are performed according to conventional conditions in the art.
[0035] Example 1
[0036] A method for preparing a carbon-based ruthenium / palladium / zirconium composite catalyst includes the following steps:
[0037] S1. Preparation of carrier activated carbon: 200g of dried furfural residue lignin (below 20 mesh) was suspended in 1200g of 30% H3PO4 solution and stirred at 25℃ for 6h. After stirring, it was dried at 105℃ for 24h, then heated to 550℃ in a muffle furnace at a heating rate of 15℃ / min and carbonized at 550℃ for 3h. After carbonization, it was quenched while hot to increase its hardness, yielding crude activated carbon. The crude activated carbon was then pulverized, and 3000mL of 0.1M HCl solution was added. The mixture was heated to 50℃ and held for 30min. Finally, it was washed with distilled water, dried at 105℃ for 24h, and ground into fine powder to obtain carrier activated carbon. The specific surface area of the carrier activated carbon prepared in this step was 1316.7m². 2 / g;
[0038] S2. Impregnation: Weigh 10g of the carrier activated carbon prepared in step S1 and add it to 40g of ruthenium nitrate solution with a concentration of 5mol / L. Stir and react for 7h, filter, place the filtered product in 100ml of water and sonicate for 13min, filter again to obtain parent material 1; add parent material 1 to 40g of palladium nitrate solution with a concentration of 2mol / L, stir and react for 4h, filter, place the filtered product in 100ml of water and sonicate for 10min, filter again to obtain parent material 2; add parent material 2 to 40g of zirconium nitrate solution with a concentration of 4mol / L, stir and react for 5h, filter, place the filtered product in 100ml of water and sonicate for 10min, filter again, and dry at 105℃ for 24h to obtain the composite catalyst precursor;
[0039] S3, Calcination and Reduction: The composite catalyst precursor prepared in step S2 was calcined at 500℃ for 3h, and then the calcined composite catalyst precursor was transferred to a fixed-bed reactor. Hydrogen gas at 6MPa was introduced at 200℃ for reduction reaction. When the reduction temperature of the fixed-bed reactor no longer changed, it was kept at the temperature for 30min. After washing three times with deionized water and drying at 105℃ for 24h, carbon-based ruthenium / palladium / zirconium composite catalyst was obtained.
[0040] The structure of the carbon-based ruthenium / palladium / zirconium composite catalyst prepared in this embodiment is as follows: Figure 1 As shown in the figure, the left image is a SEM image and the right image is an EDS image. The SEM image shows the microstructure of the carbon-based ruthenium / palladium / zirconium composite catalyst, while the EDS image shows the distribution of metal ions on the surface of the carbon-based ruthenium / palladium / zirconium composite catalyst.
[0041] Depend on Figure 1 It can be seen that in the carbon-based ruthenium / palladium / zirconium composite catalyst prepared in this embodiment, the metallic ruthenium / palladium / zirconium are uniformly distributed on the carbon surface. The uniform and widespread distribution of the active metals in the catalyst is beneficial to improving the catalytic efficiency of the catalyst.
[0042] Example 2
[0043] A method for preparing a carbon-based ruthenium / palladium / zirconium composite catalyst includes the following steps:
[0044] S1. Preparation of carrier activated carbon: 300g of dried furfural residue lignin (below 20 mesh) was suspended in 1800g of 25% H3PO4 solution and stirred at 25℃ for 6h. After stirring, it was dried at 105℃ for 24h, and then heated to 550℃ in a muffle furnace at a heating rate of 15℃ / min. The carbonization reaction was carried out at 550℃ for 3h. After the carbonization reaction was completed, it was quenched while hot to increase its hardness, and crude activated carbon was obtained. The crude activated carbon was then pulverized, and 3000mL of 0.1M HCl solution was added to it. The mixture was heated to 50℃ and held for 30min. Finally, it was washed with distilled water, dried at 105℃ for 24h, and ground into fine powder to obtain carrier activated carbon.
[0045] S2. Impregnation: Weigh 10g of the carrier activated carbon prepared in step S1 and add it to 40g of ruthenium nitrate solution with a concentration of 6mol / L. Stir and react for 6h, filter, place the filtered product in 100ml of water and sonicate for 15min, filter again to obtain parent material 1; add parent material 1 to 40g of palladium nitrate solution with a concentration of 2mol / L, stir and react for 4h, filter, place the filtered product in 100ml of water and sonicate for 10min, filter again to obtain parent material 2; add parent material 2 to 60g of zirconium nitrate solution with a concentration of 4mol / L, stir and react for 4h, filter, place the filtered product in 100ml of water and sonicate for 10min, filter again, and dry at 105℃ for 24h to obtain the composite catalyst precursor;
[0046] S3, Calcination and Reduction: The composite catalyst precursor prepared in step S2 was calcined at 500℃ for 3h, and then the calcined composite catalyst precursor was transferred to a fixed-bed reactor. Hydrogen gas at 6MPa was introduced at 200℃ for reduction reaction. When the reduction temperature of the fixed-bed reactor no longer changed, it was kept at the temperature for 30min. After washing three times with deionized water and drying at 105℃ for 24h, carbon-based ruthenium / palladium / zirconium composite catalyst was obtained.
[0047] Example 3
[0048] A method for preparing a carbon-based ruthenium / palladium / zirconium composite catalyst includes the following steps:
[0049] S1. Preparation of carrier activated carbon: 150g of dried furfural residue lignin (below 20 mesh) was suspended in 900g of 35% H3PO4 solution and stirred at 25℃ for 6h. After stirring, it was dried at 105℃ for 24h. Then, it was heated to 550℃ in a muffle furnace at a heating rate of 15℃ / min and carbonized at 550℃ for 3h. After the carbonization reaction, it was quenched while hot to increase its hardness, and crude activated carbon was obtained. The crude activated carbon was then pulverized, and 3000mL of 0.1M HCl solution was added to it. The mixture was heated to 50℃ and held for 30min. Finally, it was washed with distilled water, dried at 105℃ for 24h, and ground into fine powder to obtain carrier activated carbon.
[0050] S2. Impregnation: Weigh 10g of the carrier activated carbon prepared in step S1 and add it to 50g of ruthenium nitrate solution with a concentration of 5mol / L. Stir and react for 4h, filter, place the filtered product in 100ml of water and sonicate for 15min, filter again to obtain parent material 1; add parent material 1 to 50g of palladium nitrate solution with a concentration of 2.5mol / L, stir and react for 5h, filter, place the filtered product in 100ml of water and sonicate for 13min, filter again to obtain parent material 2; add parent material 2 to 70g of zirconium nitrate solution with a concentration of 4mol / L, stir and react for 4h, filter, place the filtered product in 100ml of water and sonicate for 10min, filter again, and dry at 105℃ for 24h to obtain the composite catalyst precursor;
[0051] S3, Calcination and Reduction: The composite catalyst precursor prepared in step S2 was calcined at 500℃ for 3h, and then the calcined composite catalyst precursor was transferred to a fixed-bed reactor. Hydrogen gas at 6MPa was introduced at 200℃ for reduction reaction. When the reduction temperature of the fixed-bed reactor no longer changed, it was kept at the temperature for 30min. After washing three times with deionized water and drying at 105℃ for 24h, carbon-based ruthenium / palladium / zirconium composite catalyst was obtained.
[0052] Example 4
[0053] A method for preparing a carbon-based ruthenium / palladium / zirconium composite catalyst includes the following steps:
[0054] S1. Preparation of carrier activated carbon: 200g of dried furfural residue lignin (below 20 mesh) was suspended in 1200g of 30% H3PO4 solution and stirred at 25℃ for 6h. After stirring, it was dried at 105℃ for 24h. Then, it was heated to 550℃ in a muffle furnace at a heating rate of 15℃ / min and carbonized at 550℃ for 3h. After the carbonization reaction, it was quenched while hot to increase its hardness, and crude activated carbon was obtained. The crude activated carbon was then pulverized, and 3000mL of 0.1M HCl solution was added to it. The mixture was heated to 50℃ and held for 30min. Finally, it was washed with distilled water, dried at 105℃ for 24h, and ground into fine powder to obtain carrier activated carbon.
[0055] S2. Impregnation: Weigh 10g of the carrier activated carbon prepared in step S1 and add it to 60g of ruthenium nitrate solution with a concentration of 5mol / L. Stir and react for 4h, filter, place the filtered product in 100ml of water and sonicate for 15min, filter again to obtain parent material 1; add parent material 1 to 50g of palladium nitrate solution with a concentration of 2.5mol / L, stir and react for 5h, filter, place the filtered product in 100ml of water and sonicate for 13min, filter again to obtain parent material 2; add parent material 2 to 70g of zirconium nitrate solution with a concentration of 5mol / L, stir and react for 4h, filter, place the filtered product in 100ml of water and sonicate for 10min, filter again, and dry at 105℃ for 24h to obtain the composite catalyst precursor;
[0056] S3, Calcination and Reduction: The composite catalyst precursor prepared in step S2 was calcined at 500℃ for 3h, and then the calcined composite catalyst precursor was transferred to a fixed-bed reactor. Hydrogen gas at 6MPa was introduced at 200℃ for reduction reaction. When the reduction temperature of the fixed-bed reactor no longer changed, it was kept at the temperature for 30min. After washing three times with deionized water and drying at 105℃ for 24h, carbon-based ruthenium / palladium / zirconium composite catalyst was obtained.
[0057] The metal content in the solution was determined by flame atomic absorption spectrometry, and the active components ruthenium, palladium, and zirconium in the carbon-based ruthenium / palladium / zirconium composite catalysts prepared in Examples 1 to 4 were detected by the difference method. The results are shown in Table 1.
[0058] Table 1
[0059]
[0060] As shown in Table 1, the content of active components is related to the immersion time of the active component solution and the duration of ultrasound. The active components that first adhere to the surface of activated carbon have an important influence on the adhesion of subsequent active components.
[0061] Example 5
[0062] A method for preparing 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane, the specific steps of which are as follows:
[0063] 100 g of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane was dissolved in 200 mL of organic solvent DMF. Hydrogen gas was continuously introduced to maintain a reaction pressure of 0.5 MPa. Then, 1 g of the carbon-based ruthenium / palladium / zirconium composite catalyst prepared in Example 1 was added, and the reaction was carried out at 25 °C and a liquid hourly space velocity of 50 h⁻¹. -1 The reaction was carried out under the specified conditions for 0.5 h to obtain 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
[0064] Example 6
[0065] A method for preparing 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane, the specific steps of which are as follows:
[0066] 100 g of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane was dissolved in 200 mL of organic solvent DMF. Hydrogen gas was continuously introduced to maintain a reaction pressure of 0.5 MPa. Then, 1 g of the carbon-based ruthenium / palladium / zirconium composite catalyst prepared in Example 1 was added, and the reaction was carried out at 25 °C and a liquid hourly space velocity of 50 h⁻¹. -1 The reaction was carried out for 1 hour under the specified conditions to obtain 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
[0067] Comparative Example 1
[0068] A method for preparing 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane, the specific steps of which are as follows:
[0069] 100 g of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane was dissolved in 200 mL of organic solvent DMF. Hydrogen gas was continuously introduced to maintain a reaction pressure of 0.4 MPa. Then, 1 g of the carbon-based ruthenium / palladium / zirconium composite catalyst prepared in Example 1 was added, and the reaction was carried out at 30 °C and a liquid hourly space velocity of 40 h⁻¹. -1 The reaction was carried out for 1 hour under the specified conditions to obtain 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
[0070] Comparative Example 2
[0071] A method for preparing 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane, the specific steps of which are as follows:
[0072] 100 g of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane was dissolved in 200 mL of organic solvent DMF. Hydrogen gas was continuously introduced to maintain a reaction pressure of 0.5 MPa. Then, 1 g of the carbon-based ruthenium / palladium / zirconium composite catalyst prepared in Example 1 was added, and the reaction was carried out at 25 °C and a liquid hourly space velocity of 50 h⁻¹. -1 The reaction was carried out for 1 hour under the specified conditions to obtain 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
[0073] Comparative Example 3
[0074] A method for preparing 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane, the specific steps of which are as follows:
[0075] 100g of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane was dissolved in 200mL of organic solvent DMF. Hydrogen gas was continuously introduced to maintain a reaction pressure of 0.5MPa. Then, 1g of a 5% carbon-based palladium catalyst (purchased as the active component) was added. The reaction was carried out at 25°C and a liquid hourly space velocity (LHSV) of 50h⁻¹ for 0.5h to obtain 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
[0076] Comparative Example 4
[0077] A method for preparing 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane, the specific steps of which are as follows:
[0078] 100 g of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane was dissolved in 200 mL of organic solvent DMF. Hydrogen gas was continuously introduced to maintain a reaction pressure of 0.5 MPa. Then, 1 g of a commercially available active component (5% carbon-based palladium / ruthenium catalyst) was added, and the reaction was carried out at 25 °C and a liquid hourly space velocity (LHSV) of 50 h⁻¹. -1 The reaction was carried out under the specified conditions for 0.5 h to obtain 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
[0079] Test case
[0080] The purity of 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane prepared in Examples 5-8 and Comparative Examples 1-2 was determined by liquid chromatography (LC). The results are shown in Table 2. The LC chromatogram of 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane prepared in Example 5 is shown in Table 2. Figure 2 As shown.
[0081] Table 2
[0082]
[0083] As shown in Table 2, the catalytic activity of the composite catalyst of the present invention is greatly affected by the content of the three active components. Based on the product purity of the examples, it can be seen that the composite catalyst exhibits the best catalytic effect when the content of the three active components approaches a certain value. The product purity of Examples 5 and Comparative Examples 1-2 indicates that pressure and space velocity are key factors affecting product purity during the preparation of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane. The optimal values are 25°C and a liquid hourly space velocity of 50 h⁻¹. -1 The optimal reaction time is 0.5 h. The purity of the products from Example 5 and Comparative Examples 3 and 4 indicates that the carbon-based ruthenium / palladium / zirconium composite catalyst provided by this invention exhibits higher catalytic reduction activity and better performance, and the prepared 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane has higher purity.
Claims
1. The application of a composite catalyst in the preparation of 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane, characterized in that, The method for preparing the composite catalyst is characterized by comprising the following steps: S1: Furfural residue lignin is suspended in H3PO4 solution and stirred at 20~30℃ for 5~8h. Then it is dried, carbonized and quenched to obtain crude activated carbon. HCl solution is added to the crude activated carbon and heated to 45~65℃ for 20~40min. After washing, drying and grinding, carrier activated carbon is obtained. The mass ratio of furfural residue lignin to H3PO4 solution is 1:6; the concentration of H3PO4 solution is 25-35%; the carbonization specifically involves heating the dried product to 550°C in a muffle furnace at a heating rate of 15°C / min, and then holding it at 550°C for 3 hours to complete the carbonization. The concentration of the HCl solution is 0.1M; the volume-to-mass ratio of the HCl solution to furfural residue lignin is 15:1, unit: mL / g; S2: Add the carrier activated carbon prepared in step S1 to the ruthenium nitrate solution, stir and react for 3-6 hours, filter, place the filtered product in water and sonicate for 10-20 minutes, filter again to obtain parent 1; wherein, the mass ratio of the carrier activated carbon to the ruthenium nitrate solution is 1:(4-8); the concentration of the ruthenium nitrate solution is 2-8 mol / L; Add parent compound 1 to palladium nitrate solution, stir and react for 3-6 hours, filter, place the filtered product in water and sonicate for 10-20 minutes, filter again to obtain parent compound 2; wherein, the mass ratio of palladium nitrate solution to carrier activated carbon is (4-8):1; Add parent material 2 to zirconium nitrate solution, stir and react for 3-6 hours, filter, place the filtered product in water and sonicate for 10-20 minutes, filter again, and dry to obtain composite catalyst precursor; wherein, the mass ratio of zirconium nitrate solution to activated carbon support is (4-8):1; S3: The composite catalyst precursor prepared in step S2 was calcined at 500℃ for 3h, and then the calcined composite catalyst precursor was transferred to a fixed bed reactor. Hydrogen gas at 6MPa was introduced at 200℃ for reduction reaction. When the reduction temperature of the fixed bed reactor no longer changed, it was kept at the temperature for 30min. After washing and drying, carbon-based ruthenium / palladium / zirconium composite catalyst was obtained. The specific application involves dissolving 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane in an organic solvent, continuously purging hydrogen gas to maintain a reaction pressure of 0.5 MPa, then adding a composite catalyst, and reacting at 25°C and a liquid hourly space velocity of 50 h⁻¹. -1 The reaction was carried out under the specified conditions for 0.5 h to obtain 2,2-bis[3-(3-aminobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
2. The application as described in claim 1, characterized in that, In S2, the mass ratio of the carrier activated carbon to the ruthenium nitrate solution is 1:6; the concentration of the ruthenium nitrate solution is 5~6 mol / L.
3. The application as described in claim 1, characterized in that, In S2, the mass ratio of the palladium nitrate solution to the activated carbon support is 6:
1.
4. The application as described in claim 1, characterized in that, In S2, the mass ratio of the zirconium nitrate solution to the carrier activated carbon is 7:
1.
5. The application as described in claim 1, characterized in that, The amount of the composite catalyst added is 0.5~1.5% of the mass of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
6. The application as described in claim 1, characterized in that, The amount of the composite catalyst added is 1% of the mass of 2,2-bis[3-(3-nitrobenzoylamino)-4-hydroxyphenyl]hexafluoropropane.
Citation Information
Patent Citations
Method for preparing catalyst for hydrogenating pyridine compound and application thereof
CN103394348A
Preparation method of furfural residue-based nitrogen-doped porous carbon material and electro-catalytic oxygen reduction performance of furfural residue-based nitrogen-doped porous carbon material
CN114023980A
Single-step catalytic preparation of para-aminophenol
US20110092740A1